Upaya mengatasi cacat produksi botol kemasan air 600 ml dengan metode Statistical Process Control - Mahros Darsin; Mochamad Asrofi; Joni Anggianto; Soesatijono Soesatijono (Institution for Industrial Research and Standardization of Industry - Padang, 2020)
This research aim is to find out the type of defects in production process of 600 ml bottle water at PT TIB Jember, then some attempts to resolve the problem. The p-chart of Statistical Process Control was employed. The control chart in September 2019 shown that some data beyond the ultimate control limit (UCL). The defects were categorized into three: whitening, deviate form, and broken. The Pareto chart revealed that the aforementioned defects were 59.7%, 26.36% and 15.07% respectively. By using the fishbone diagram some root cause of the defects were found. First, the unstable workplace temperature which disturbs the preform melting process prior to blowing, therefore causing whitening the bottle. Second, the heater which is often turned off while processing that caused deviate form. The frequently turned off the heater was caused by cracked-damage along with the hoses of overdue. Some suggestions were given, one of them was replacing the hoses by the new ones. The new control chart in October 2019 showed that all data within the limits following the replacement of the hose. It also reduced the rate of the defect by 0.19% from 0.74% to 0.55%.